Immobilization of Actively Thromboresistant Assemblies on Sterile Blood‐Contacting Surfaces. Issue 1 (21st June 2013) - Qu, Zheng; Krishnamurthy, Venkat; Haller, Carolyn A.; Dorr, Brent M.; Marzec, Ulla M.; Hurst, Sawan; Hinds, Monica T.; Hanson, Stephen R.; Liu, David R.; Chaikof, Elliot L.
<x xml:space="preserve">Abstract</x> Rapid one‐step modification of thrombomodulin with alkylamine derivatives such as azide, biotin, and PEG is achieved using an evolved sortase (eSrtA) mutant. The feasibility of a point‐of‐care scheme is demonstrated herein to site‐specifically immobilize azido‐thrombomodulin on sterilized commercial ePTFE vascular grafts, which exhibit superior thromboresistance compared with commercial heparin‐coated grafts in a primate model of acute graft thrombosis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>